Vigor of plantain plants (Musa AAB cv. Harton) and its relationship with physical, chemical and biological characteristics of the soil - González García, Hebandreyna (2021)
Introduction. The southern zone of lake Maracaibo is the region with the biggest area and highest volume of plantain (cv. Hartón) production in Venezuela, aspect that motivates the study of various properties of the local soil. Objective. To evaluate the physical, chemical and biological characteristics of the soil associated with the vigor of the Musa AAB cv. Harton. Materials and methods. Seven farms representative of the region were selected, in which lots with high (AV) and low vigor (BV) were determined, by evaluating number of hands per bunch (NMR), circumference of the pseudostem of the mother plant (CPM) and height of the succession plant (AHS). Different physical, chemical and biological characteristics of the soil were determined in experimental units of 1000 m2 for each lot of vigor evaluated. Results. The results of the studied variables allowed to categorize contrasting lots of vigor in the plantain crop. Regarding the relationship with edaphic characteristics, significant and negative correlations were found between percentage of sand, bulk density, basic and instantaneous infiltration with NMR, AHS and CPM. Positive correlations between silt percentage and soil moisture were obtained with NMR. Considering the chemical characteristics, there were no significant correlations. Regarding biological variables, negative correlations were found between total population of phytonematodes with NMR and CPM. Microbial carbon showed positive correlations with CPM and AHS. The principal component analysis allowed determining the grouping of batches of AV and BV, and their correlation with edaphic variables with greater weight in the expression of the variability of the results. Conclusion. The identification of edaphic variables associated with the vigor of plantain crop allows to show the characteristics that must be considered for the efficient management of the soil and its effect on the development of plantain.